Pharmacokinetics of dexmedetomidine in pediatric patients undergoing cardiac surgery with cardiopulmonary bypass. Issue 4 (16th January 2023) - Kim, Eun‐Hee; Choi, Byung‐Moon; Kang, Pyoyoon; Lee, Ji‐Hyun; Kim, Hee‐Soo; Jang, Young‐Eun; Ji, Sang‐Hwan; Noh, Gyu‐Jeong; Cho, Joo‐Youn; Kim, Jin‐Tae
Abstract: Background: Cardiopulmonary bypass can affect the pharmacokinetics of anesthetic agents. Aims: We aimed to evaluate the pharmacokinetics of dexmedetomidine for infants and small children undergoing cardiac surgery with cardiopulmonary bypass based on population pharmacokinetics. Methods: We enrolled 30 pediatric cardiac surgical patients in this study. After anesthetic induction with atropine (0.02 mg/kg), thiopental sodium (5 mg/kg), and fentanyl (2–3 μg/kg), we administered 1 μg/kg of dexmedetomidine for 10 min, followed by administration of 0.5 μg/kg of dexmedetomidine per hour during surgery. At the initiation of cardiopulmonary bypass, 1 μg/kg of dexmedetomidine was infused over 5 min. Arterial blood was obtained at predefined time points. A pharmacokinetic model was developed using NONMEM. Theory‐based allometric scaling with fixed exponents was applied. Weight, age, post‐menstrual age, fat‐free mass, whether to implement cardiopulmonary bypass and temperature were explored as covariates. Results: A total of 376 blood samples were obtained from 29 children (age: 20.3 ± 19.3 months, weight: 9.7 ± 4.1 kg). A two‐compartment mammillary model with third compartment associated cardiopulmonary bypass procedure best explained the pharmacokinetics of dexmedetomidine. The pharmacokinetic parameter estimates (95% CI) standardized to a 70‐kg person were as follows: V1 (L) = 31.6 (17.9–39.5), V2 (L) = 90.1 (44.0–330), Cl (L/min) = 1.08 (0.70–1.25), Q (L/min) = 2.0 (1.05–3.46). Volume for third compartment associated cardiopulmonary bypass procedure (L) = 39.4 (19.3–50.9). Clearance was not influenced by the presence of cardiopulmonary bypass in this model. Conclusion: When cardiopulmonary bypass is applied, the plasma concentration of dexmedetomidine decreases due to an increase in the volume of distribution, so a loading dose is required to maintain the previous concentration.